2018
DOI: 10.13057/biodiv/d190520
|View full text |Cite
|
Sign up to set email alerts
|

Protein and fatty acid profile of marine fishes from Java Sea, Indonesia

Abstract: Priatni S, Ratnaningrum D, Kosasih W, Sriendah E, Srikandace Y, Rosmalina T, Pudjiraharti S. 2018. Protein and fatty acidprofile of marine fishes from Java Sea, Indonesia. Biodiversitas 19: 1737-1742. Indonesia is the second largest producer of capturefisheries products in the world and the most capture fisheries production comes from marine fisheries. Marine fish is a source of protein,amino acid, saturated and unsaturated fatty acids, which are important components of diet. The objective of the study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
5
1
2
Order By: Relevance
“…These authors also reported that total protein content in Pampus argenteus was 61.07% weight by weight. In the present study, it is found that the total protein content is only 18.28% in P. argenteus (w/w) indicating that its protein content is far less when compared to the total protein content reported for the same species by Priatni et al (2018); this huge variation could be attributable to the size, age, and food sources available to the species in the habitat where individuals of this species live. Further, the total protein content is also at low level in P. chinensis and P. niger, it is 16.24% (w/w) in the former and 19.58% (w/w) in the latter.…”
Section: Inventory Of Marine Fishery Resources Of Coastline Of Andhra Pradeshcontrasting
confidence: 68%
See 1 more Smart Citation
“…These authors also reported that total protein content in Pampus argenteus was 61.07% weight by weight. In the present study, it is found that the total protein content is only 18.28% in P. argenteus (w/w) indicating that its protein content is far less when compared to the total protein content reported for the same species by Priatni et al (2018); this huge variation could be attributable to the size, age, and food sources available to the species in the habitat where individuals of this species live. Further, the total protein content is also at low level in P. chinensis and P. niger, it is 16.24% (w/w) in the former and 19.58% (w/w) in the latter.…”
Section: Inventory Of Marine Fishery Resources Of Coastline Of Andhra Pradeshcontrasting
confidence: 68%
“…Sikorski (1990) stated that among all the fishes, marine fish are very important sources of protein and different mineral components. Priatni et al (2018) analyzed total protein content in nine marine fish species, Leiognathus equulus, Mystacoleucus padangensis, Nemipterus hexodon, Oxyleotris marmorata, Selaroides leptolepis, Terapon jarbua, and Trichiurus lepturus; the protein content in these fish species varied from 65 to 86% weight by weight. These authors also reported that total protein content in Pampus argenteus was 61.07% weight by weight.…”
Section: Inventory Of Marine Fishery Resources Of Coastline Of Andhra Pradeshmentioning
confidence: 99%
“…This high marine biodiversity has become essential for various marine bioactive natural products, including protein and peptides (Chasanah, 2008;Fawzya & Irianto, 2020;Putra & Murniasih, 2016). Nine major marine fish obtained from one of the main fishing ports in Indonesia contained up to 86.56% total protein (Priatni et al, 2018). Moreover, its marine by-products, such as fish skin obtained from red snapper, contained easily digested collagen peptides (Wibawa et al, 2015).…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 99%
“…Perbedaan ini selain karena proses pengolahan yang berbeda juga karena bahan sambal serta jenis ikan yang berbeda. Kandungan protein ikan bete-bete (Leiognathus sp) pada beberapa penelitian adalah 66,58% (Priatni et al 2018) dan 73,87-77,07% (Jayabalan dan Ramamoorthi 1984), sedikit lebih tinggi bila dibandingkan dengan kandungan protein ikan lele (Clarias sp) yaitu 39,59-43,87% (Siagian dan Nugroho 2017) dan 53,10-67,21% (Chukwu dan Shaba 2009).…”
Section: Hasil Dan Pembahasan Komposisi Proksimat Sambal Ikan Bete-beteunclassified